(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The purpose of this study was to think about research to improve students’ vocabulary skills by listening to English songs at SMK Bina Nusantara Cisalak. In this way it is able to improve the ability of students to constrain vocabulary.Ã‚Â English songs are considered an effective and fun way to teach vocabulary, as they can provide pleasure or challenge for students in learning vocabulary. Methods used in this study by way of research Class actions. This class action is cyclical, Ã‚Â based each learning meeting must be improved. If there is still no improvement in cycle 1 or cycle 2 can be done in cycle 3 until there is an increase in learning. Ã‚Â With this research is able to improve students’ ability to treasure vocabulary. Further increase students’ motivation in learning English in a fun way. Teachers should provide motivation and knowledge to students to improve their skills in English especially in vocabulary memorization to help students more easily learn English. Suggest that learning English is easy and fun .Ã‚Â By listening English songs it is easier to remember the English vocabulary of each lyric. The more frequently repeating listening EnglishÃ‚Â song the easier it will be to memorize the English vocabulary of the song’s lyrics. Not only memorizing English vocabulary but can be applied also by speaking to say the words of the song lyrics.Ã‚Â So not only listening English songs but can make it easier to communicate using English because it often hears so must remember often.Ã‚Â